2018
DOI: 10.15640/ijgws.v6n1a9
|View full text |Cite
|
Sign up to set email alerts
|

Gender Assessment of Watermelon Production among Farmers in Ibarapa Area of Oyo State

Abstract: The study conducted gender assessment of watermelon production among farmers in Ibarapa area of Oyo state. One hundred and thirty-two respondents were randomly selected. Data collected were analysed using descriptive and inferential. The result revealed that 66.4% of the respondents were males, 70% were educated, 69.5% were married and 88.3% fell between ages 30-50 years, 46.9 percent had 6-10 years of experience. 93% male were involved in weeding than their female counterparts. However, more female (81.3%) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
2
2
0
Order By: Relevance
“…This finding is supported by the results of the descriptive analysis which shows that male youth experience higher crop losses compared with female youth (Figure 3). This finding is in agreement with [39] in their studies in Oyo State, Nigeria, who reported that there is a significant difference in losses experienced by male and female farmers in watermelon production. The similarities could emanate from the common practice of assigning females to engage in postharvest activities like sorting and grading compared with their male counterparts in rural areas of Africa.…”
Section: Results Of the Shapiro-wilk Testsupporting
confidence: 92%
“…This finding is supported by the results of the descriptive analysis which shows that male youth experience higher crop losses compared with female youth (Figure 3). This finding is in agreement with [39] in their studies in Oyo State, Nigeria, who reported that there is a significant difference in losses experienced by male and female farmers in watermelon production. The similarities could emanate from the common practice of assigning females to engage in postharvest activities like sorting and grading compared with their male counterparts in rural areas of Africa.…”
Section: Results Of the Shapiro-wilk Testsupporting
confidence: 92%
“…This finding agrees withOdebode (2007) who reported that adult males are engaged in land clearing, planting and weeding, while adult females carried out the seed selection and post-harvest practices in melon production. Many of the respondents (46.70%) had http://dx.doi.org/10.7770/safer-V6N1-art1318…”
supporting
confidence: 92%
“…Home gardening, in general, refers to the cultivation of a small plot of land that is often located nearby or within walking distance of the family home. Home gardens may be thought of as a mixed cropping system that includes vegetables, fruits, plantation crops, spices, herbs, decorative and medicinal plants, as well as livestock that can be used as an additional source of food and revenue [4].…”
Section: About Home Gardensmentioning
confidence: 99%
“…The total dietary diversity score (DDS) ranges from 0 to 7. The DDS scores were categorized into three categories including low dietary diversity score (0-2), moderate dietary diversity score (3)(4)(5), and high dietary diversity score of more than 5.…”
Section: Sampling Proceduresmentioning
confidence: 99%